2002
DOI: 10.1073/pnas.152330599
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase-associated protein SGT1 is required for host and nonhost disease resistance in plants

Abstract: Homologues of the yeast ubiquitin ligase-associated protein SGT1 are required for disease resistance in plants mediated by nucleotide-binding site͞leucine-rich repeat (NBS-LRR) proteins. Here, by silencing SGT1 in Nicotiana benthamiana, we extend these findings and demonstrate that SGT1 has an unexpectedly general role in disease resistance. It is required for resistance responses mediated by NBS-LRR and other R proteins in which pathogen-derived elicitors are recognized either inside or outside the host plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
392
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(423 citation statements)
references
References 42 publications
26
392
1
4
Order By: Relevance
“…Transient expression: Rx tagged with four HA epitope tags was constructed in the pB1 binary vector containing the Rx promoter and 39 sequence (Rx:4HA) as described (Bendahmane et al 2002;Peart et al 2002b). The NBLet sequence was deleted by overlapping PCR to create Rx: 4HADNBLet.…”
Section: Methodsmentioning
confidence: 99%
“…Transient expression: Rx tagged with four HA epitope tags was constructed in the pB1 binary vector containing the Rx promoter and 39 sequence (Rx:4HA) as described (Bendahmane et al 2002;Peart et al 2002b). The NBLet sequence was deleted by overlapping PCR to create Rx: 4HADNBLet.…”
Section: Methodsmentioning
confidence: 99%
“…The mutant alleles used for the construction of double mutants with pen3-1 were coi1-1 (Col-6 background [Feys et al, 1994]), npr1-1 (Cao et al, 1994), sid2-1 (Nawrath and Mé traux, 1999), pad4-1 (Glazebrook and Ausubel, 1994), eds1-1 (Ws-0 background [Parker et al, 1996]), Etr1-1 (Bleecker et al, 1988), jar1-1 (Staswick et al, 1992), edr1 (Frye and Innes, 1998), sgt1b-1 (Ler background [Peart et al, 2002]), rar1-10 (Ler background ), NahG (Lawton et al, 1995), pen1-1 (Collins et al, 2003), and pen2-3 (Lipka et al, 2005). All of the mutant lines, unless noted otherwise, were in the Col-0 background.…”
Section: Double Mutant Constructionmentioning
confidence: 99%
“…Among the mutants with defects in the salicylic acid (SA) signal transduction pathway, nonhost resistance was diminished in eds1 mutants and transgenic plants with the bacterial NahG gene relative to wild-type plants (Parker et al, 1996;Mellersh and Heath, 2003;Yun et al, 2003;Zimmerli et al, 2004). Using virus-induced gene silencing, the chaperone and chaperone-like proteins HSP70, HSP90, and SGT1, which are thought to stabilize resistance (R) proteins and act upstream of EDS1, were shown to contribute to nonhost resistance in Nicotiana benthamiana (Peart et al, 2002;Kanzaki et al, 2003). Mutants with defects in the ethylene/jasmonate (ET/ JA) signal transduction pathways exhibited wild-type levels of nonhost resistance in Arabidopsis thaliana, even though there is evidence from microarray studies that this pathway is preferentially induced after inoculation of plants with some inappropriate pathogens (Huitema et al, 2003;Zimmerli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from several groups indicated that SGT1 is required by a diverse range of R genes from different plant species in response to a variety of pathogens [61,[92][93][94][95]. In yeast, SGT1 is a key regulatory protein in centromere function and cell cycle transition and is associated with SKP1 to regulate the activity of the SCF E3 ligase complex [96].…”
Section: U-box-type E3 Ligases Are Newly Identified Members Of the Ubmentioning
confidence: 99%